Spectroscopic study of solvent effects on the electronic absorption spectra of flavone and 7-hydroxyflavone in neat and binary solvent mixtures - Sancho, Matías I. (2011)
The solvatochromic characteristics of flavone and 7-hydroxyflavone were investigated in neat and binary solvent mixtures. The spectral shifts of these solutes were correlated with the Kamlet and Taft parameters (α, β and π*) using linear solvation energy relationships. The multiparametric analysis indicates that both specific hydrogen bond donor ability and non-specific dipolar interactions of the solvents play an important role in absorption maxima of flavone in pure solvents. The hydrogen bond acceptor ability of the solvent was the main parameter affecting the absorption maxima of 7-hydroxyflavone. The simulated absorption spectra using a TD-DFT method were in good agreement with the experimental ones for both flavones. Index of preferential solvation was calculated as a function of solvent composition. Preferential solvation by ethanol was detected in cyclohexane-ethanol and acetonitrile-ethanol mixtures for flavone and in acetonitrile-ethanol mixtures for 7-hydroxyflavone. These results indicate that intermolecular hydrogen bonds between solute and solvent are responsible for the non-linear variation of the solvatochromic shifts on the mole fraction of ethanol in the analyzed binary mixtures.